Efektivitas Model Pembelajaran Snowball Throwing dan Talking Stick Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Agus Apriyanto; Suharno Suharno; Siti Kamsyiati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
This research is a quantitative research that aims to determine whether the SnowballThrowing learning model can influence learning outcomes of Matehematics that are better andmore effective than the Talking Stick learning model on addition and subtraction of variousfractions students in grade V. The research used the eksperimental research method whit pretestpost-test control group design. Its population was all of students in Grade V of StatePrimary School in target area Imam Bonjol of Laweyan Sub-district in Academic Year2017/2018. Cluster Random Sampling was used to determine its samples. They consisted ofthe students in Grade V of State Primary School Totosari No.102 and students in Grade V ofState Primary School Tunggulsari I No.72.the data of research were collected through test oflearning result in Mathematics. Prior to application, the test was experimented at State PrimarySchool Tunggulsari II No.179. they were analyzed by using the statistical t test at the signifikanlevel of 0.05. the result of the research shows that the aplplication of the Snowball Throwingand Talking Stick learning model can affect the students’ learning result in mathematics.((thitung = 2,056; t < - 1,989atau t > 1,989). The results of this study it can be concluded thatstudents who are taught with the Snowball Throwing model have learning outcomes in additionmaterial and a reduction in various forms of fractions better than student learning outcomesthat are taught with the Talking stick model.